Information security behaviour : a descriptive analysis on a Malaysian public university - Ramlah Hussein, *; Fateema Lambensa; Raja Baharuddin Anom (2011)
The critical issues of information security have gradually increased. Effective information security management require a great understanding both technological and human dimensions. Thus, the purpose of this research is to investigate the university student?s behavior towards information security and to examine factors influencing information security behavior. The study adopted the quantitative approach by conducting a survey among students in one of the public universities in Malaysia. Questionnaires were distributed to the targeted respondents. Then, the SPSS software was used to systematically analyze all data obtained and generate statistical information and detailed analyses of the survey results. This study is helpful in exploring issues related to information security behavior. Hopefully, this study contributed to an understanding of the influencing factors towards the university students? behavior in relation to information security.